2015
DOI: 10.1177/2151458514567314
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of a Geriatric Hip Fracture Program in India for Femoral Neck Fracture

Abstract: Geriatric hip fractures are a challenging clinical problem throughout the world. Hip fracture services have been shown to shorten time to surgery, decrease the cost of admissions, and improve the outcomes. We instituted a geriatric hip fracture program for comanagement of these injuries by orthopedic and internal medicine teams at our hospital in India. From January 2010 till December 2011, 119 patients with a femoral neck fracture were treated with cemented modular hemiarthroplasty under this program using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Even if we presume that all of the patients lost to follow-up (11 patients) had died, the 1-year mortality rate of our study will be less than 18%, which is still comparable to those reported in the Western studies. In another domestic study, Jain et al20) followed up patients with a very similar geriatric hip fracture. In the study, the 6-month mortality was 6% and the 2-year rate was 10.9%, which are comparable to our 1-year rate of 7.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Even if we presume that all of the patients lost to follow-up (11 patients) had died, the 1-year mortality rate of our study will be less than 18%, which is still comparable to those reported in the Western studies. In another domestic study, Jain et al20) followed up patients with a very similar geriatric hip fracture. In the study, the 6-month mortality was 6% and the 2-year rate was 10.9%, which are comparable to our 1-year rate of 7.7%.…”
Section: Discussionmentioning
confidence: 99%
“…6 – 8 Few studies elicit the problem of hip fractures in India, highlighting the clinical and socioeconomic challenges in the management of hip fractures. 20 , 21 On admission, the prime target would be to optimize the patient for surgery, needing the care of an orthogeriatric team, as rightly highlighted by Lau et al, Jain et al, and Rocca et al 20 , 22 , 23 Identifying the key elements in this orthogeriatic assessment is of vital importance to provide a targeted approach for individual patient, as highlighted by popular established guidelines. 6 – 8 , 24 Our search of literature showed that controversy exists in deciding between HHA and THA when considering patient’s age, with evidence supporting both.…”
Section: Discussionmentioning
confidence: 99%
“…Hip fracture programme was implemented by Deepak Jain et al study which showed goal of early surgery, mobilisation and discharge from hospital with decreased mortality is achievable in Indian setting. 14 44.9% patients received preoperative transfusions and 20.57% patients received postoperative, this was as per the liberal transfusion protocol followed in our Institution wherein preoperatively Hb was raised to 10 and postoperatively patient received transfusion if Hb was less than 8 or severe pallor, major bleeding intraop. As we know, allogeneic blood transfusion is associated with significant cost and risks there is need to follow restricted transfusion protocol, wherein patient receives transfusion only if Hb is less than 7 which is safe and effective as per Cochrane review.…”
Section: Discussionmentioning
confidence: 99%